Pemeriksaan Gangguan Daya Ingat di Usia Madya - Konginan, Agustina (ANIMA Indonesian Psychological Journal, 2008)
Addiction on the Internet occurred when time allocated to play or using the Internet for non-work activities reach a disturbing or even destroying level towards everyday activities, i.e. work activities, study, social activities, or significant decline of productivity and academic achievement. We should be alerted to such condition, when someone allocates more than 10 hours every day for the activity. A first step to treat is recognizing the symptoms. The computer-game and video-game addiction symptoms in both children and adults are exposed in this article. The American Medical Association considers to assume this addiction condition as a medical ailment or part of a certain mental disorder such as depression or anxiety. Ketergantungan (adiksi) pada Internet terjadi bila waktu yang digunakan untuk bermain atau menggunakan Internet untuk keperluan di luar pekerjaan mencapai level yang mengganggu bahkan “merusak” aktivitas wajar sehari-hari, yaitu aktivitas bekerja, sekolah, maupun kegiatan sosial, dan turunnya produktivitas kerja dan prestasi belajar secara bermakna. Perlu diwaspadai kemungkinan kondisi adiksi bila seseorang melakukan kegiatan tersebut lebih dari 10 jam setiap harinya. Langkah awal untuk penyembuhan adalah mengenali gejala-gejalanya. Dalam artikel ini dipaparkan gejala adiksi computer-game dan video-game pada anak serta orang dewasa. American Medical Association mempertimbangkan kondisi adiksi game ini sebagai gangguan medis atau merupakan bagian dari gangguan jiwa tertentu seperti depresi atau gangguan cemas.